THE STUDY OF THE IMPACT OF SOCIAL MOVEMENT ON INDIA’S ECONOMY - PURSHOTTAM KUMAR MAHTO (International Journal of Multidisciplinary Research and Studies, 2020)
In every culture, both in the past and in the present, social movements have taken place and will continue to do so in the foreseeable future. Their type, extent, and frequency might vary quite a little from one another. Social movements were responsible for defining the state throughout the early phases of the process of political creation. This included the state's responsibilities, obligations, and responsibility, as well as its political borders. In addition to this, they played an important role in the distribution of power between the several subgroups that make up society as a whole. In more recent times, they have been especially important in the battle against authoritarian regimes, as well as the Church and feudal authority, as well as external standards and rules. Events such as the French and Russian revolutions, the Indian independence fight, and various peasant uprisings have had a substantial impact on our way of life and contributed significantly to its development. Movements such as Nazism in Germany, Islamism in the Middle East, Hindutva in India, and Tamil nationalism in Sri Lanka have had an impact not only on the political structure of those countries but also on the value systems of the people living in such nations. Their legacies continue to have an effect on each and every one of us in a variety of distinct ways. In today's day and age, situations similar to this may take place in any state. They typically play a role that decides the outcome of political contests in all political systems, regardless of whether they are democratic or authoritarian; however, this is not always the case. They are accountable for the establishment and dismantling of political institutions, in addition to the standards of social and political conduct and the nature of regimes.